1991
DOI: 10.1111/j.1471-4159.1991.tb06355.x
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin and Iron Uptake by the Brain: Effects of Altered Iron Status

Abstract: Transferrin (Tf) and iron uptake by the brain were measured in rats using 59Fe-125I-Tf and 131I-albumin (to correct for the plasma content of 59Fe and 125I-Tf in the organs). The rats were aged from 15 to 63 days and were fed (a) a low-iron diet (iron-deficient) or, as control, the same diet supplemented with iron, or (b) a chow diet with added carbonyl iron (iron overload), the chow diet alone acting as its control. Iron deficiency was associated with a significant decrease and iron overload with a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
84
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 134 publications
(90 citation statements)
references
References 43 publications
6
84
0
Order By: Relevance
“…Also, cellular replication in the brain of the rat, especially in capillary and glial cells, occurs most rapidly during the first 2-3 weeks of life [27,28]. With respect to iron supply it was found that variations in dietary iron lead to changes in iron and transferrin uptake by the brain, increasing with iron depletion and decreasing with iron loading [29]. However, age-dependent changes in transferrin uptake were not eliminated.…”
Section: Iron Transport Into the Developing Brainmentioning
confidence: 88%
“…Also, cellular replication in the brain of the rat, especially in capillary and glial cells, occurs most rapidly during the first 2-3 weeks of life [27,28]. With respect to iron supply it was found that variations in dietary iron lead to changes in iron and transferrin uptake by the brain, increasing with iron depletion and decreasing with iron loading [29]. However, age-dependent changes in transferrin uptake were not eliminated.…”
Section: Iron Transport Into the Developing Brainmentioning
confidence: 88%
“…Following translocation to early endosomes, iron dissociates from transferrin and is transported to the cytoplasm or directly to the mitochondria. In the brain, iron uptake mediated by TfR participates in iron transport through the blood-brain barrier (6), and the density of TBI-binding sites correlates well with the regional distribution of TfR expression on the luminal surface of endothelial cells. However, TBI-binding sites and TfR expression only loosely correlate with the final steady-state distribution of iron (7).…”
Section: Dopaminergic Cell Death In the Substantia Nigra (Sn) Is Centmentioning
confidence: 96%
“…The brain has two potential mechanisms to increase iron delivery to iron-starved neurons. The more general mechanism would be to increase total brain iron delivery from the serum via the blood-brain and the blood-CSF-brain interfaces (10,26). This mechanism seems to be the normal response of the more mature animal where brain iron uptake increases 2-fold in response to dietary iron deficiency (26).…”
Section: Discussionmentioning
confidence: 99%
“…The more general mechanism would be to increase total brain iron delivery from the serum via the blood-brain and the blood-CSF-brain interfaces (10,26). This mechanism seems to be the normal response of the more mature animal where brain iron uptake increases 2-fold in response to dietary iron deficiency (26). This process would be dependent on the vascular endothelial cell of the blood-brain barrier, the choroid plexus epithelial cell of the blood-CSF barrier, and the ependymal cell of the CSF-brain barrier being able to sense the total iron status of the brain.…”
Section: Discussionmentioning
confidence: 99%